Analyzing the effectiveness of digital marketing in building a brand image for the Mulyosari Group - Raihany, Lutfia; Sawitri, Dewi Khrisna (PT. Riset Press International, 2024)
Research on the use of digital marketing is an important component in running a business in the current era of society 5.0. In this research, an analysis of the effectiveness of the many types of digital marketing that can be applied by online shop business people is carried out so that they can maximize sales while providing a brand image to customers. This research aims to find out which type of digital marketing is most effective in providing a brand image to customers at the Mulyosari Group. The research method used in this research is a qualitative approach, data collection was carried out through interviews, observation and surveys. The results of data testing show that the most effective digital component used to build a brand image at the Mulyosari Group is marketing through video content, so it is necessary to maximize the creation of marketing content in the form of video. Components that must be improved in video content are in terms of planning, taking videos and posting them to social media. Mulyosari Group's video content must be able to create a brand image for its customers in order to increase product sales.